Disputas territoriais camponesas: as experiências agroecológicas no Assentamento Cunha em Cidade Ocidental, GO - Silva, Edson Batista da (2014)
The present study has the objective to understand the experiences in Cunha agroecological settlement as a result of the peasant struggle with agribusiness in order to stay on land. To achieve it we use the bibliographical and documentary research, and fieldwork with conducting semi-structured and structured interviews, besides the direct observation in the field notes, and photographic records. In this sense, the research was based on a wide understanding, who believes in the existence of disparate projects for the field. Meanwhile, the conquest of the Cunha farm, appropriate / dominated by agribusiness was essential to give other uses through Agroecology. However, the territorial settlement involved production disputes MST with its constituent base, which was co-opted by the state, supported by CONTAG. This process resulted in the provision of unfavorable Agroecology limits, with the difficult to control of inputs and direct marketing channel, reality aggravated by the action of Agribusiness on the settlement, both directly with borderline monoculture in the municipality of Cristalina, such as indirect with the determination of the direction of agricultural policy. Associated to the pressure of the financial/property capital of the national metropolis, Brasilia. The analysis of the actors of agroecological production, the collective experience of the "Eldorado dos Carajás" is the result of a policy network in defense of Agroecology. The experience of Integrated Sustainable Agroecology Production (PAIS) is a result of the institutional proposed peasant permanence on land, these add up traditional knowledge and territoriality of settled peasant families that promotes peasant agriculture with the principles of agroecology. The network inside the settlement, changing the seeds, knowledge, and others, the networks of the peasant settlement with external actors, as Brazilian Agricultural Research Agency (EMBRAPA) allowed the relative autonomy of inputs, but the farms remain submitted to the user and commercial capital. However, the adoption of agroecology allowed the revision of the society / nature, the strengthening of the struggle for the sovereignty food and the territorial agrobiodiversity.